2022
DOI: 10.1101/2022.06.25.497608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TREE-QMC: Improving quartet graph construction for scalable and accurate species tree estimation from gene trees

Abstract: Genome-scale data is increasingly available for species tree estimation, bringing attention to the fact that different regions of the genome can have evolutionary histories that differ from each other and from the species tree due to incomplete lineage sorting. This has led to the development of many new methods, some of which estimate the species tree from a collection of (estimated) gene trees. ASTRAL, the dominant method in this class, executes an exact algorithm for the Maximum Quartet Support Species Tree… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This result has driven methodological development over the last decade, with some of the most popular approaches to date being based on quartets (Larget et al 2010;Mirarab et al 2014). Moreover, new and improved quartet-based methods are continually being developed (Mirarab and Warnow 2015;Zhang et al 2018;Dibaeinia et al 2021;Mahbub et al 2021;Han and Molloy 2023). Similar results exist for triplets (rooted, binary, three-leaf trees); see Degnan and Rosenberg (2006); Liu et al (2010); Islam et al (2020).…”
Section: Introductionmentioning
confidence: 97%
“…This result has driven methodological development over the last decade, with some of the most popular approaches to date being based on quartets (Larget et al 2010;Mirarab et al 2014). Moreover, new and improved quartet-based methods are continually being developed (Mirarab and Warnow 2015;Zhang et al 2018;Dibaeinia et al 2021;Mahbub et al 2021;Han and Molloy 2023). Similar results exist for triplets (rooted, binary, three-leaf trees); see Degnan and Rosenberg (2006); Liu et al (2010); Islam et al (2020).…”
Section: Introductionmentioning
confidence: 97%
“… Le et al (2021) explored different variants of constrained-INC ( Zhang et al 2019 ) and found unsatisfactory gene tree accuracy and optimistic species tree quality when compared to conventional phylogenetic tree building approaches, despite the fact that just one model condition in their experiment included more than 1000 sequences. Han and Molloy (2023) have recently developed TREE-QMC, which is based on wQMC and offers a fast method for constructing the quartet graph directly from input gene trees without the need for explicitly computing the weighted quartet distributions as in the case of wQMC and wQFM.…”
Section: Introductionmentioning
confidence: 99%